Environmental law in ukraine: present and prospects - YASHCHUK, Sergii (Journal of Education, Technology and Computer Science, 2013)
The state policy in the field of ecology should be based on sustainable system of law, legal acts, norms, but this system, especially during the transition should be flexible, that is able to respond quickly on changes of surrounding components, to be able to adapt to changes of too complex environment. And this is very effective means for overcoming the environmental crisis and ensuring the environmental function of the state.